Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Air Minum Dalam Kemasan (Amdk) Merek Aqua - Zabidatus, Zahwa; Sudarnice, Sudarnice; Rahmat, Yuliawan; Aprilia, Tasya (Jurnal Pustaka Manajemen (Pusat Akses Kajian Manajemen), 2023)
This study aims to determine the instrument validity of product quality and price on purchasing decisions for bottled drinking water (AMDK) brand Aqua. The price and quality of Aqua drinking water have a close relationship. Consumers need to consider various factors, such as water quality, packaging, service, personal needs, and available promos, before buying Aqua. So this makes researchers interested in doing this research. The method in this study uses quantitative scientific methods by applying ex post facto, which has independent variables (variables that influence) and dependent variables (variables that are influenced), with the population in this study being 74 students in Surabaya. Data collection in the study used a questionnaire which was then tested for validity using SPSS. The results in this study use a validity test at a significant level of 5%, resulting in 9 valid statement items and 1 statement said to be invalid for the product quality variable (X1) and price (X2) because r-count> must be greater than < r-table and there are 4 valid statement items and 1 invalid statement item for the Aqua bottled water purchase decision variable (Y) because r-count> must be greater than < r-table.